Sounding the sacred in the age of fake news – Practical theology reflecting on the public sphere - Kloppers, Elsabé (HTS teologiese studies, 2020)
The public sphere, in which religion is lived and in which religious singing functions, is briefly discussed and related to manipulated truths and ‘fake news’ regarding the use of spiritual songs and hymns as religious and cultural offerings, with reference especially to texts displaying a disregard for responsible hermeneutical principles. A plea is made not only for a practical theology that engages critically with the fundamentals of the current culture and the use of religious symbols in public, but also for a sounding theology that reflects on communication through singing and other forms of art in the public space of worship as well as in the more ‘visible’ public sphere whilst creating beauty in the process of reflection. Through this means, spaces of resonance could be opened where people become participants drawn in into a performance of practical theology, reflecting together on the religion they live and finding new ways of voicing their faith in the public sphere, unveiling aspects of authenticity and truth.Contribution: From an interdisciplinary perspective fitting the scope of the journal, it is shown how hymns, texts and music draw people into a performance of a practical theology reflecting on lived religion, while finding new ways of performing the sacred in the public sphere – in the process thus opening up aspects of truth in a world of fake news.